Oxygen uptake and heart rate response of 6 standardized tennis drills - Bekraoui, N.; Fargeas-Gluck, M.-A.; Léger, L. (Applied Physiology, Nutrition, and Metabolism, 2012)
The purpose of this study was to compare the oxygen uptake of various on-court tennis drills. Eleven tennis players were monitored with a portable metabolic device to measure oxygen uptake of 6 different tennis drills at low and high speeds. The 6 drills were done with or without striking the ball, over half or full-width of the court, in attack or defense mode, using forehand or backhand strokes. Oxygen uptake values (mean ± SD) ranged from 33.8 ± 4.2 to 42.3 ± 5.1 mL·kg-1·min-1 when running at low speed on the full-width court in defense mode without striking the ball and when running at high speed on the full-width court in attack mode while striking the ball, respectively. Specific differences were observed. Attacking mode requires 6.5% more energy than defensive playing mode. Backhand strokes demand 7% more energy at low speed than forehand ones. Running and striking the ball costs 10% more energy than running without striking the ball. While striking the ball, shuttle running on half-width court costs 14% more energy than running on full-width courts. The specificity of the oxygen uptake responses obtained for these various tennis drills gives an improved representation of their energy cost and could be used to optimize training loads.